Dekonstruksi Citra Keluarga Sakinah Dalam Pernikahan Dengan Pasangan Narcissistic Personality Disorder Dalam Sudut Pandang Hukum Islam - Wati, Dewi Setio; Nurnazli, Nurnazli; Zaelani, Abdul Qodir (Universitas Sang Bumi Ruwa Jurai, 2025)
This study examines the impact of Narcissistic Personality Disorder (NPD) on achieving a harmonious family in marriage, and reviews the approach of Islamic family law and psychology in dealing with the problem. This study uses a library study method, This study describes how NPD characteristics, such as egoism and lack of empathy, can disrupt household harmony. In addition, this study also discusses the role of Islamic family law in providing protection for couples involved in marriages with individuals who have NPD characteristic disorders. The results of the study show that marriage with an NPD partner often creates emotional and psychological imbalances that hinder the achievement of a harmonious family, so it requires a multidisciplinary approach to resolve it